Peranan dan sumbangan JAKIM dalam dialog antara agama - Mahfuzah Zohdi; Yusri Mohamad Ramli; Jaffary Awang (Universiti Kebangsaan Malaysia, 2014)
The Department of Islamic Development Malaysia or officially known in its Malay form as Jabatan Kemajuan Islam Malaysia (JAKIM) always been seem to has did a little in participating itself in dialogue between different beliefs. As an authoritative and governmental representative of Islam, JAKIM is craved by the religious societies especially Muslims to be more exposed and championing itself in interfaith dialogue to foster mutual understanding as well as comprehend the societies about Islam and tie up relationship with other religious communities. Therefore its involvement in the Committee for Promoting Understanding and Harmony among Religious Adherents or Jawatankuasa Mempromosikan Persefahaman dan Keharmonian di antara Penganut Agama (JKMPKA) seem to be a big step forward for JAKIM to be more active in dialogue. This case study analyse the role and contribution of JAKIM in interfaith dialogue since its inception till today. This qualitative study collected data by documenting information through interviews and observations as well as studying archive of JAKIM’s files and documents relating to the subject. All data then be analysed by using ‘Atlas.ti’ software to better organise them in classified themes. This study shows that JAKIM did involve in interfaith dialogue albeit limitedly since its early establishment. The programs of interfaith dialogue organised by JAKIM are conducted whether in direct way which is a direct dialogue between religions such as Mosque Tour Guide and interfaith discourses, or indirect way by and large limited to a single religious community but related to interfaith issues such as mission carried by JAKIM to rural areas as well as interfaith course in Muslim College of London. Recent development shows a better development with the participation in JKMPKA although its role is limited as a mediator between Muslim NGOs.